Revenue from matching platforms - Philip Marx; James Schummer (Theoretical Economics, 2021)
We consider the pricing problem of a platform that matches heterogeneous agents using match-contingent fees. Absent prices, agents on the short side of such markets capture relatively greater surplus than those on the long side (Ashlagi et al. 2017). Nevertheless we show that the platform need not bias its price allocation toward either side. With independently drawn preferences, optimal price allocation decisions are independent of market size or imbalance; furthermore, changes in the optimal price level move both sides' prices in the same direction. In contrast, preference homogeneity biases price allocation in a direction that depends on the form of homogeneity; furthermore, changes in market imbalance move both sides' prices in opposite directions. These effects arise due to the exclusivity of matchings in two-sided market settings.
Keywords: D40; C78; 330; Pricing; matching; platforms